2011
DOI: 10.1007/s11695-011-0544-5
|View full text |Cite
|
Sign up to set email alerts
|

Does Exercise Improve Weight Loss after Bariatric Surgery? A Systematic Review

Abstract: Bariatric surgery leads to significant weight loss in the obese patient. Exercise has been shown to improve weight loss and body composition in non-surgical weight loss programmes. The role of exercise to improve weight loss following bariatric surgery is unclear. The objective of this review is to systematically appraise the evidence regarding exercise for weight loss in the treatment of obesity in bariatric surgery patients. MEDLINE, AMED, CINAHL, EBM Reviews (Cochrane Database, Cochrane Clinical Trials Regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(101 citation statements)
references
References 32 publications
5
90
0
6
Order By: Relevance
“…Peak VO 2 relative to body weight was importantly increased in all studies where it was reported [23-25, 28], but without indicating the amount of weight loss that is significant. In addition, in previous studies major postoperative increases in physical activity were seen after sleeve gastrectomy, and these findings were associated with greater weight loss and improved quality of life [36, 37]. The same outcome was observed in our study population but after RYGB surgery.…”
Section: Discussionsupporting
confidence: 87%
“…Peak VO 2 relative to body weight was importantly increased in all studies where it was reported [23-25, 28], but without indicating the amount of weight loss that is significant. In addition, in previous studies major postoperative increases in physical activity were seen after sleeve gastrectomy, and these findings were associated with greater weight loss and improved quality of life [36, 37]. The same outcome was observed in our study population but after RYGB surgery.…”
Section: Discussionsupporting
confidence: 87%
“…Our data highlight the need for additional randomized controlled exercise trials to better understand the implications of components of exercise prescription (dose, duration, intensity) on long-term weight loss maintenance and health in RYGB surgery patients. Increased physical activity after bariatric surgery has been reported to provide additional weight loss (43). However, most of these studies were nonrandomized, retrospective, and observational in nature and measured physical activity by questionnaire and self report (43), methods that may lead to overestimation of exercise participation in obese subjects (44,45), including those who have undergone bariatric surgery (29).…”
Section: Discussionmentioning
confidence: 99%
“…Increased physical activity after bariatric surgery has been reported to provide additional weight loss (43). However, most of these studies were nonrandomized, retrospective, and observational in nature and measured physical activity by questionnaire and self report (43), methods that may lead to overestimation of exercise participation in obese subjects (44,45), including those who have undergone bariatric surgery (29). Our observations using a semi-supervised exercise intervention are in line with those of Shah et al, who showed that a high-volume exercise prescription following bariatric surgery had no impact on body weight and waist circumference when patients were compared with a control group (20).…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review 15 of 17 observational studies suggest that exercise is associated with greater weight loss following bariatric surgery [2]. Besides the increased weight loss effect it has also been shown that regular physical activity decreases mortality in obese persons [3].…”
Section: Introductionmentioning
confidence: 99%